Les temporalités de l’éducation internationale : Pratiques et technologies de l’accélération sociale - Bolay, Matthieu; Rey, Jeanne (Anthropologica, 2019)
Schools are places where specific temporalities are enacted daily through teaching practices both inside and outside the classrooms. This paper, which draws on ethnographic research in more than fifteen international private schools in Switzerland, looks at the accelerated temporality that prevails in these schools. International private schools have been expanding massively in Switzerland since the 2000s. We suggest that international schools, which explicitly forge a link between the cosmopolitan condition and uncertainty as a context of learning, train students to be autonomous and to be able to cope with the exigencies of flexibility and mobility that characterize the model of the multinational corporation. In this context, the article argues that it is through the temporal dimension of teaching technologies in international schools that the initial social advantages of students are maintained and enhanced. The process of autonomisation that we describe take several forms – temporal and spatial – which constitute the two axes of the article: the first addresses the accelerated temporality in the space of the school, and the other looks at the effects of the spatial reordering of the school upon learning temporalities. Finally, we discuss the ambivalent position of teachers towards these temporal transformations, wavering between belief in their emancipatory potential and increasing precarity of employment conditions.